Representations of Karelians and the Karelian language in Karelian and Russian local newspapers - Tanczos, Outi Maria (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2017)
Peer reviewed